Human Resource Well-Being Management in Islamic Education: A Study at Kuttab Fatih Indonesia - Didih Syakir Munandar; Jaja Jahari; Bambang Samsul Arifin; Karman Karman (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The purpose of this study is to examine how human resource well-being is managed at Kuttab Fatih Indonesia. Using a qualitative approach with a case study design, the research employed in-depth interviews, field observations, and document analysis to gain comprehensive insights. Findings indicate that the well-being program implemented at Kuttab Fatih encompasses psychological, social, spiritual, and financial dimensions. The policies introduced within this framework seek to establish balance between professional responsibilities, personal life, religious guidance, and economic support. Such integration demonstrates the program’s ability to enhance teacher motivation, strengthen loyalty, and improve overall productivity, thereby reflecting its effectiveness. The evidence underscores the critical role of human resource well-being in advancing both staff performance and teacher commitment. Based on these findings, it is recommended that Kuttab Fatih continue to refine its well-being management strategies, particularly by acknowledging external factors that may influence financial sustainability and by ensuring alignment with well-being models rooted in Islamic principles. Moreover, the study suggests that other Islamic-based educational institutions could adopt this approach as a reference when formulating comprehensive and culturally appropriate well-being policies designed to foster motivation, engagement, and professional growth among educators and staff members. Other Islamic educational institutions should refer to this study as a guide while creating thorough well-being policies.